FUNGSI PENGAWASAN TERHADAP PEREDARAN KOSMETIK BERBAHAN TERLARANG PADA BALAI PENGAWAS OBAT DAN MAKANAN KOTA KENDARI (Studi Kasus Pasar Sentral Kota Kendari) - Abdul Kadir; Taufik Taufik; Rahayu Rahayu (Journal Publicuho, 2021)
This study aims to determine and describe the function of controlling the circulation of prohibited cosmetics at the Food and Drug Supervisory Agency (BPOM) Kendari City (Central Market Case Study of Kendan City). conclusions/verification. The results showed that Drugs and Food (BPOM) Kendani City in terms of carrying out activities carried out according to previously established standards have been carried out properly, namely carrying out intensification or inspections to places where there are indications that there are prohibited cosmetics containing ingredients.  And the aspect of carrying out monitoring is not optimal because some people who are still unfamiliar with gadgets or applications cannot use BPOM Mobile, this application can be used before buying cosmetics so that they are not only tempted by instant results but also pay attention to whether the cosmetics are safe or not.  Has been carried out properly, supervision through print media and social media to educate the public about choosing cosmetic products that are safe and free of prohibited substances. In terms of taking corrective actions if they get deviations from obstacles, they are not optimal, because there are still some people who are less cooperative if they know of cosmetics containing prohibited substances.